Influence of laser photocoagulation on choroidal capillary cytoarchitecture. Issue 1 (1st January 2001) - Guymer, Robyn H; Hageman, Gregory S; Bird, Alan C
Abstract : AIM: To identify if laser photocoagulation induces morphological changes specifically related to the choroidal capillary endothelial processes that protrude into Bruch's membrane. METHODS: Two human eyes and one adult macaque monkey eye received retinal laser photocoagulation that was just suprathreshold, before enucleation or exenteration. They were examined by electron microscopy to determine the length of the endothelial processes emanating from the choroidal capillaries in the region around the laser burn. One human and two monkey untreated eyes were used for comparison. RESULTS: In human eyes, there was no increase in the number of processes 15 hours after laser treatment but at 5 days the processes were more numerous and longer within 400–500 μm of the burn than in the untreated half of the same eye. The processes were longer 9 days after photocoagulation in the monkey, when compared with untreated monkeys, and some breached the elastic lamina, a phenomenon not seen in the untreated eyes. Qualitative differences were also noted in the endothelial cell processes following photocoagulation. Neovascularisation was not observed. CONCLUSIONS: Protrusion of choroidal endothelial cell processes into Bruch's membrane is a normal anatomical feature but the number, length, and morphology of the processes change following mild photocoagulation. It is plausible that these processes may play a part in the clearance of debris from Bruch's membrane, and represent an early stage of angiogenesis. If the latter is true prophylactic laser photocoagulation at just suprathreshold levels may carry a risk of inducing choroidal neovascularisation.